Pembuktian Gugatan Sederhana terhadap Putusan Niet Onvankelijk Verlaard Ditinjau dalam Asas Actori Incumbit Onus Probatio: (Studi Kasus Putusan Pengadilan Negeri Muara Bungo Nomor: 26/Pdt.G.S/2020/Pn. Mrb) - Luqman Hakim (Jurnal Hukum Lex Generalis, 2023)
It is hoped that this simple lawsuit can accommodate the value of justice for all Indonesian people, bearing in mind that until now there are many civil cases in the District Court where the litigants are classified as financially disadvantaged. In the Verdict of Judgment Number: 26/Pdt.G.S/2020/PN.Mrb the Defendant submitted the argument that his child experienced psychological trauma in writing and verbally without any medical evidence, in evidentiary law it is known as the actori incumbit onus probadio principle, namely whoever argues must prove. The case is of course a contradiction where Plaintiff can prove the existence of a default, on the other hand, Defendant presented rebuttal arguments without being supported by evidence. The Defendant's argument was accommodated in the Decision which resulted in an unacceptable simple lawsuit (Niet Onvanjelijk Verlaard). The research method used is normative which means that the data used in this research uses secondary data. The results and conclusions of this study are the principle of Actori Incumbit Onus Probatio which means that whoever has a right or puts forward his argument must prove the existence of that right or argument as stipulated in Article 163 HIR. However, in the case as stated in Decision Number: 26/Pdt.G.S/2020/PN. Mrb, Defendant argued that his child had suffered psychological trauma due to Plaintiff's behavior but could not prove the existence of such psychological trauma from a medical perspective. On the other hand, the Plaintiff was able to prove his simple claim, but the examining judge accommodated the Defendant's argument so that he decided that the Plaintiff's simple claim could not be accepted (Niet Onvankelijk Verlaard) because the proof, in this case, was not simple.